Perbedaan Perkembangan Motorik Bayi Pasca Pemberian Stimulasi Pijatan dan Berenang - Aryunani Aryunani; Pipit Festi Wilianarti (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2016)
Developmental growth disorders in children under five will result in a decrease in the formation of attitudes and behavior of children in the future. These disorders can be prevented by stimulating development. This study used a quasy experimental design. This research was carried out for 4 months in Privately Practising Midwives in Sidotopo village of Semampir sub-district of North Surabaya with a sample of infants aged 6 to 12 months. Data sampling used consecutive sampling collected through observation using the observation sheet. Data were analyzed using Wilcoxon test to see the difference in gross motor before and after treatment in the treatment group. In the treatment group 40% infant experienced an increase of 1-2 segment of motor development and 60% had an increase of 3-4 segments.